PEGylation of Recombinant Human Deoxyribonuclease I Provides a Long‐Acting Version of the Mucolytic for Patients with Cystic Fibrosis. Issue 2 (25th October 2020) - Guichard, Marie‐Julie; Wilms, Tobias; Mahri, Sohaib; Patil, Harshad P.; Hoton, Delphine; Ucakar, Bernard; Vanvarenberg, Kevin; Cheou, Pamela; Beka, Mathilde; Marbaix, Etienne; Leal, Teresinha; Vanbever, Rita
Abstract: Inhalation of recombinant human deoxyribonuclease I (rhDNase) is a gold‐standard therapy in the management of cystic fibrosis (CF). Yet, the rapid elimination of the mucolytic from the lungs requires its daily administration and rhDNase contributes to the high therapy burden of patients. Here, a long‐acting version of rhDNase that is delivered once weekly instead of once daily is presented. Conjugation of rhDNase to a polyethylene glycol (PEG) chain sustains its presence and mucolytic activity within murine lungs for more than 15 days. One single dose of PEGylated rhDNase is as effective as 1 daily dose of unconjugated rhDNase during five days to decrease the DNA content in the lungs of β‐ENaC mice, a model of the CF lung disease. Moreover, once weekly administration of PEGylated rhDNase over four weeks decreases both the DNA content and the neutrophil counts in the lungs of β‐ENaC mice. PEGylated rhDNase is stable to jet nebulization. Finally, multiple high‐dose administrations of PEGylated rhDNase for up to 3 months do not cause any significant pulmonary or systemic toxicity, nor accumulation of the rhDNase or PEG moieties in biological fluids. PEGylation of rhDNase may offer a convenient long‐acting mucolytic to patients with CF. Abstract : PEGylation of recombinant human deoxyribonuclease I is shown to be an efficient method to fine‐tune the behavior of the enzyme and can provide significant benefits to patients with cystic fibrosis: a sustained presence and mucolytic activity in the lungs, suggesting the possibility of therapeutic efficacy following weekly—instead of daily—dosing. Moreover, no toxicity is observed in mice following high‐dose administrations and protein integrity is fully preserved following jet nebulization.